The visual magnocellular deficit in Chinese-speaking children with developmental dyslexia - Qian, Yi; Bi, Hong-Yan (Frontiers in Psychology, 2014)
Many alphabetic studies have evidenced that individuals with developmental dyslexia (DD) have deficits in visual magnocellular(M) pathway. However, there are few studies to investigate the M function of Chinese DD. Chinese is a logographic language, and Chinese characters are complicated in structure. Visual skills and orthographic processing abilities are particularly important for efficient reading in Chinese as compared to alphabetic languages. Therefore, it is necessary to investigate the visual M function of Chinese DD and whether the M function was associated with orthographic skills. In the present study, 26 dyslexic children (mean age: 10.03 years) and 27 age-matched normal children (mean age: 10.37 years) took part in a coherent motion detection task and an orthographic awareness test. The results showed that dyslexic children had a significantly higher threshold than age-matched children in coherent motion detection task. Meanwhile, children with DD responded more slowly in orthographic awareness test, although the group difference was marginally significant. The results suggested that Chinese dyslexics had deficits both in visual M pathway processing and orthographic processing. In order to investigate the relationship between M function and orthographic skills, we made a correlation analysis between coherent motion threshold and orthographic awareness by merging performance of dyslexic children and age-matched children. The results revealed that coherent motion thresholds were positively correlated with reaction times in orthographic awareness test, suggesting that better magnocellular function was related to better orthographic processing skills.